PENGARUH DISIPLIN DAN LINGKUNGAN KERJA NON-FISIK TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA DINAS PEMERINTAH KABUPATEN NGANJUK - Sari, Meylany Ulfa; Sugiono, Sugiono; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to examine the variables that affect employee performance with independent variables, discipline and non-physical work environment through satisfaction with Prime Bank Government Services. government. The technique of determining the sample is the Slovin purpose sampling method with the number of respondents being 58 people. The data collection method used a questionnaire with a Likert scale that met the validity and reliability requirements. The data analysis technique used is a quantitative descriptive analysis technique that uses path analysis. The results of the study show that it does not partially prove that discipline affects the performance of Nganjuk district government employees. It is proven that partially or simultaneously job satisfaction and non-physical work environment affect employee performance. So that job satisfaction is able to mediate the increasing influence of discipline variables and non-physical work environment on the performance of service employees.